The role of Malassezia sp, sebum level and Trans Epidermal Water Loss (TEWL) toward the dandruff severity between hijab and non hijab wearing subjects - Kristiana Etnawati; Agnes Sri Siswati; Satiti Retno Pudjiati; Devi Artami Susetiati; Dwi Retno Adiwinarni; Affendi Purbananto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Dandruff is a common symptom in adolescence, which possibly due to increasing ofMalassezia sp. colonization, sebum level as well as skin hydration. Wearing hijab ispredicted to increase the humidity and sebum level lead to increase the number ofMalassezia sp. and dandruff severity. A case-control study was conducted on 19 femalewith dandruff who wear hijab and 19 female with dandruff who do not wear hijab, agebetween 18 and 27 years old. The dandruff severity was defined clinically using ascoring system (0-100), only subjects with minimum score of 28 will be included in thisstudy. The sebum and trans epidermal water loss (TEWL) levels were measured withSebumeter and Tewameter from Courage Khazaka. The Malassezia sp. was examinedusing microscopic examination of the squama and culture in the Saboraud medium.There were no significant differences found between hijab and non-hijab groups fordandruff severity. No difference found between two groups for sebum level, Malasseziasp. number microscopically, and Malassezia sp. colonization. Only TEWL level in hijabgroup that was found to be higher than non-hijab group. Wearing hijab does not increasethe dandruff severity, sebum level and colonization number of Malassezia sp. Wearinghijab is found to increase the TEWL level.